(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Screening of salinity tolerance genotypes of rice on the basis of its phenotypic performance alone is not much reliable and will take more time in progress in breeding process. Molecular marker-based screening eases this process. An experiment was carried out with 22 diverse rice genotypes in Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to study their salt tolerance at both seedling and reproductive stages. On the basis of yield and yield contributing traits, genotypes were categorized as tolerant, moderately tolerant and susceptible. The genotypes RC 227, RC 229, RC 191, Binadhan-8, Binadhan-10, Binadhan-11 and FL-478 were found as tolerant, while Binadhan-7 and BRRI dhan39 were found as susceptible. Grain weight hill-1 was found highly significant. Plant height, total tiller hill-1, grain weight panicle-1, 1000 grain weight and all other traits except sterile spikelets panicle-1 were showed a positive correlation with grain weight hill-1. Selected four salt linked SSR markers viz. AP3206f, RM1287, RM7075 and RM10793 were used to determine salinity tolerance. The genetic diversity was ranges from 0.6116 to 0.7810 with an average of 0.6663. The highest PIC value was 0.7524 and the lowest was 0.4762 from AP3206f and RM7075, respectively. The UPGMA clustering system generated four genetic clusters. The highest genetically dissimilarity of (Cluster 1) vs (Cluster 3) and the crossing would be helpful for salt tolerant rice development. Thus, selected SSR primers and genotypes would be useful in marker assisted selection (MAS), quantitative trait loci (QTL) mapping, gene pyramiding and ultimately improvement of salt tolerant rice varieties. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 176-183